2013
DOI: 10.2478/s11686-013-0123-0
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite loci-based distribution of Trypanosoma cruzi genotypes from Chilean chronic Chagas disease patients and Triatoma infestans is concordant with a specific host-parasite association hypothesis

Abstract: The objective of this study was to investigate if there is specific host-parasite association in Chilean populations of Trypanosoma cruzi. For this purpose, two groups of parasites were analyzed, one from chronic chagasic patients, and the other from Triatoma infestans triatomines in three regions of the country. The first group consisted of four types of samples: parasites from peripheral blood of non-cardiopathic T. cruzi infected patients (NB); parasites from their corresponding xenodiagnosis (NX); parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…Previous studies provide evidence that hosts do not circulate all parasite populations all the time, in addition to segregation of infra-populations in different tissues and blood [16, 25, 27]. These studies clearly demonstrate that in vitro or in vivo passage of parasite populations further selects for haplotypes, which bias interpretation of genetic diversity [61, 62].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies provide evidence that hosts do not circulate all parasite populations all the time, in addition to segregation of infra-populations in different tissues and blood [16, 25, 27]. These studies clearly demonstrate that in vitro or in vivo passage of parasite populations further selects for haplotypes, which bias interpretation of genetic diversity [61, 62].…”
Section: Discussionmentioning
confidence: 92%
“…An additional and more pressing problem for analyzing T.cruzi ’s genetic diversity, variation, or structuring from a landscape perspective is the fact that, in general, most data are generated from culture or laboratory animal selected populations (parasite isolates). These difficulties to analyze parasite populations in all hosts have created voids in knowledge of intra-host and metapopulation dynamics, in addition to limitations from study designs and sampling methods, including ex-host selection (in vitro or in vivo) documented previously [2527]. …”
Section: Introductionmentioning
confidence: 99%
“…In the first publication, using kDNA Southern blots, more than 75% of the results in both groups were described as ‘TcI + TcII + hybrid’ [197] , perhaps reflecting cross-reactivity between minicircle hybridization probes [200] . Subsequent papers presenting nuclear microsatellite genotyping from patients from the same clinical trial, with unspecified degrees of overlap, demonstrated a predominance of TcI (79% of 33 IND and 57% of 28 CCM in [198] ; 86% of 28 IND and 71% of 24 CCM in [199] ).…”
Section: Chronic Chagas Diseasementioning
confidence: 99%